AUDIT MANAJEMEN ATAS FUNGSI OPERASIONAL PADA PT. RUANG PERKASA MANDIRI JAKARTA BARAT - Dirvi Surya Abbas; Alya Melsa Luna; Chaerul Anam; Chika Amanda; Devina Ika; Elvina Shepia Hardianti; Faiz Dzikrullah; Mutia Khalisah; Rara Andini (JURNAL RISET AKUNTANSI TIRTAYASA, 2025)
Management audit of operational functions at PT Ruang Angksa Mandiri aims to evaluate the effectiveness and efficiency in managing various operational functions of the company, including production, distribution, human resource management, and the use of technology and information systems. According to Arens et al. (2014), management audit is a systematic process to assess and improve the way management carries out operational functions to achieve the company's strategic goals. This is in line with the view of Mautz and Sharaf (2001), which states that management audits do not only focus on internal control, but also on the overall evaluation of the policies and procedures implemented. In the context of PT Ruang Angksa Mandiri, management audits play an important role in identifying potential risks and inefficiencies in operations, as well as providing recommendations to improve company performance. Furthermore, according to Maher et al. (2015), management audits also help ensure that companies comply with regulatory standards and increase transparency, which is very important in highly regulated sectors such as the aviation and space industry. With the results of this audit, companies can improve resource management, improve internal control, and strengthen competitiveness in the market.